PENGARUH LEVERAGE, LIKUIDITAS, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Sektor Tekstil dan Garmen Yang Terdaftar Di BEI Tahun 2021-2025) - Monisca Nema; Mukhzarudfa Mukhzarudfa; Scheilla Aprilia Murnidayanti (Jurnal Akuntansi Kompetif, 2026)
Introduction/Main Objectives: This study aims to analyse the influence of Leverage, liquidity, and Sales Growth on Financial Distress in textile and garment companies listed on the Indonesia Stock Exchange between 2021 and 2024. Background Problems: This study was motivated by the increasing risk of Financial Distress among companies due to industry competition and unstable economic conditions. The research question is whether Leverage, liquidity, and Sales Growth influence Financial Distress, both individually and collectively. Novelty: The novelty of this study lies in the examination of these three variables in the textile and apparel sector for the 2021–2024 period, a topic that has received limited research attention. Research Methods: This study employs a quantitative method using secondary data in the form of company financial statements obtained from the official IDX website, which were analyzed using multiple linear regression. Finding/result: The results of the study indicate that, both individually and collectively, Leverage, liquidity, and Sales Growth have an impact on Financial Distress. Conclusion: This study concludes that these three variables can be used as indicators to predict Financial Distress and serve as considerations for management and investors in their decision-making.